Gambaran Pengetahuan Ibu Hamil Tentang Kebutuhan Seksual Selama Masa Kehamilan - Lilis Kamilah; Emmy Fitrianingsih (JOURNAL EDUCATIONAL OF NURSING(JEN), 2019)
The sexual aspect is taboo and rarely reviewed by health workers, especially regarding sexual needs during pregnancy. Many people believe that sexual intercourse during pregnancy can cause miscarriage and uterine infections. As a result they do not have sexual relations during pregnancy. Sexual intercourse is safe if the pregnancy is in a normal and healthy condition. The research method used is descriptive exploratory method using purposive sampling of 80 pregnant women. The results of the study are made a frequency table then conclusions are drawn. The results of the study concluded that the majority of pregnant women with less knowledge of 50 people (62.5%) had an understanding of the knowledge of sexual needs during pregnancy so they did not have sexual relations during pregnancy. So expect communication, openness, support and understanding between husband and wife as well as communication with health workers to obtain information about ways and positions of sexual relations during pregnancy so that the psychological needs of husband and wife are met. Keywords: Knowledge, Sexual Needs, Pregnancy Period